Nanocomposites based on pH-sensitive hydrogels and chitosan decorated carbon nanotubes with antibacterial properties - Bellingeri, Romina; Mulko, Lucinda; Molina, Maria; Picco, Natalia; Alustiza, Fabrisio Eduardo; Grosso, M. Carolina; Vivas, Adriana; Acevedo, Diego F.; Barbero, Cesar A. (2018)
The present work aimed to study the properties of a novel nanocomposite with promising biomedical applications. Nanocomposites were prepared by the addition of different concentrations of chitosan decorated carbon nanotubes to acrylamide-co-acrylic acid hydrogels. The nanocomposites chemical structure was characterized by Fourier Transform Infrared Spectroscopy (FT-IR). The FT-IR shows the typical bands due to the hydrogel and additionally the peaks at 1750 cm−1 and 1450 cm−1 that correspond to the carbon nanotubes incorporated into the polymer matrix. Mechanical properties and swelling measurements in different buffer solutions were also performed. The nanocomposites showed improved mechanical properties and a stronger pH-response. In order to evaluate antimicrobial activity, the growth and adhesion of Staphylococcus aureus to nanocomposites were studied. Cytocompatibility was also evaluated by MTT assay on MDCK and 3T3 cell lines. The nanocomposites were found to be cytocompatible and showed a reduced bacterial colonization.